Video game play and computer self-efficacy: college students in computer related and non computer related disciplines - Buse, Alleta Carol, author; Makela, Carole, advisor (Colorado State University. Libraries, 2009)
The purpose of this dissertation was to gain new insight into video game playing, exposure, and preferences as well as perceptions toward success with computers between students in computer related disciplines (CRD) and students in non computer related disciplines (NCRD). Perceptions toward success with computers were measured using a slightly modified Computer Self-Efficacy scale developed by Cassidy and Eachus with questions about video game play exposure and preference included. Surveys were administered to 379 undergraduate students in college classrooms at five universities in the south region of the United States. Students were separated into four groups-CRD female, CRD male, NCRD female, NCRD male-based upon responses to gender and academic major. Comparisons were made among the groups using chi-square and independent t-tests. Logistic regressions were used to examine the predictive influence of Computer Self-Efficacy (CSE), Video Game Play (VGP), exposure, and preferences on the major group (CRD/NCRD).

Computer self-efficacy, based on Bandura's self-efficacy theory, is defined as one's perception of computer ability. The overall theory states that increased CSE may lead to increased use of computers. Studies have related CSE to increased enrollments in CRD and have shown males to have higher CSE scores than females. This study challenged the outcomes of previous studies by finding no significant differences in male and female CSE scores. Academic discipline, not gender, was found to be related to CSE.

Video games were defined and assumptions that VGP enhances CSE and influences enrollments in CRD were examined. This study found a significantly larger percentage of males than females played video games with no significant differences in CSE scores between males and females. And, no significant differences were found in VGP between students in CRD and NCRD. VGP was not found to explain males in CRD. VGP explained CRD for females, however no VGP exposure or preference variables explained CRD for females.

It appears that video game play has little influence on students being in computer related disciplines. Efforts to recruit students into computer related disciplines through the use of video game play may not be as effective as other recruitment approaches.
Keywords: career choice; college students; computer self-efficacy; gender; video game; school counseling; higher education; computer science; computer and video games; college students